Anopheles (Diptera: Culicidae) diversity in Kavre District of Nepal - Karkee, Rajendra (Journal of Natural History Museum, 2008)
A preliminary study was carried out to estimate Anopheline diversity in Kavre in June 2000. Mosquitoes were collected by using mouth aspirator and torchlight, and mounted on a triangular paper. One hundred and sixty eight individuals of Anopheles comprising eight species were collected in all. These included two species incriminated as Malaria vector - Anopheles fluviatilis and A. maculatus. The maculatus group appeared to play important role in transmitting the malaria causing focul outbreak of the disease. Key words: Anopheles; diversity; malaria; Nepal J. Nat. Hist. Mus. Vol.22, 2005 p.28-31